Improper program management-induced system archetypes - Sales, Luciano da Silva Bastos (2017)
Projects and programs: those two concepts are not one same side of a coin or even two different sides of a same coin. Despite the growing consensus among the project management community around the differences between the two topics, many organizations still fail to adopt a governance framework that considers such differences. The consequence is a domino effect: programs are treated as large projects, short-term focus values only the delivery of capabilities by component projects, an unhealthy internal competition between said projects is established, the organization's resources are burdened, and ultimately, organizations fail to realize benefits to their full potential. In this paper, we show that such situation fits into two well-known system archetypes, namely "Success to the Successful" and "Tragedy of the Commons". As case-study, we present a large, multi-year, multi-million Brazilian Government initiative, as well as the results achieved by said initiative, before and after a proper governance framework was in place. We also use System Dynamics (SD) to simulate and demonstrate said results, but also to forecast the expected results for the years yet to come, now that the programs and projects are given the proper treatment.